EXTRACTION OF FLAVONOID FROM VARIOUS PARTS OF COUROUPITAGUIANENSIS AND ITS EFFICACY AGAINST PATHOGENIC BACTERIA - Akther, Tahira; Khan, Mohd Shahanbaj; S, Hemalatha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Quantitative, qualitative, high performance liquid chromatography (HPLC) analysis of flavonoids content from different parts of CouroupitaÂ guianensis and antibacterial activity against various pathogenic bacteria. Methods: Different parts of C. guianensis such as leaves, stem bark, flower anther, flower petals, fruit rind, and fruit pulp were collected and usedÂ for extraction Â of active constituents. The phytochemical analysis was conducted to identify the presence of flavonoids in different plant parts. TheÂ amount of flavonoids were analyzed by quantitative analysis. Furthermore, HPLC analysis was performed to isolate and identify the flavonoids fromÂ the different parts. The methanol extract of different plant parts was also used to test the antibacterial efficacy in different human bacterial pathogens. Results: Flavonoids demonstrate a wide range of biochemical and pharmacological effects. In this study, we identified the flavonoids content inÂ different parts of C. guianensis. The HPLC analysis has significantly proved the presence of flavonoids in different plants parts and amount of flavonoidsÂ differs in different parts of the plant. The results also showed the significant efficacy of its extract to the different pathogenic bacterial strains. Conclusion: Our study suggested that C. guianensis is a richer source of flavonoids and due to a higher amount of flavonoids; it may have enormousÂ potential to scavenge the free radicals, oxidative damage of cell during different stresses including bacterial infections. We also suggested that HPLCÂ analysis is efficient method to isolate and identify the different compounds and study can further extend to identify and isolate the different novelÂ compounds from C. guianensis. Keywords: Couroupita guianensis, High performance liquid chromatography, Flavonoids, Antibacterial activity.